“Efficiency of SCL Via Google Classroom on Female Pre-service Teachers' Teaching Readiness (Journal of the College of Basic Education, 2025)
This study intends to examine the efficiency of student-centered learning (SCL) through Google classroom in enhancing the readiness of fourth stage females’ pre-service teachers. The research employs a quasi-experimental design with a control and experimental group to compare the teaching readiness of participants before and after the intervention. The participants were 30 of fourth stage students at the University of Baghdad - College of Education for Women/the department of English and data were collected through observation checklist to assess their teaching experience and questionnaires to assess their perceptions towards using Google Classroom. Two sections were selected, C as a control group and D as the experimental one each with (15) participants. At the beginning of the experiment, both groups have been equalized in some variables, then all students have been tested by using observation checklist to measure their readiness. The researcher applied the students-centered learning in the class and electronically through google classroom on the experimental group. At the end of the experiment, the researcher retested students by observation checklist to measure their readiness to teach through structured visits at their schools observing their teaching with their real students. Then the researcher collected the students’ perceptions towards using Google Classroom. The findings elucidated the positive impact of student-centered learning that can be obtained on Google classroom in comparison with the traditional methods being used. The results showed that students are highly motivated through the student-centered approach and it enriches their knowledge, autonomy, collaboration, engagement and experiences for future teaching as well as their readiness is highly advantageous with student centered learning than with the previous methods used.